Cult of Equestrian Saints and al-Muqawqis - Frantsouzoff, Serge A. (Scrinium, 2025)
The author of the article offers another attempt to explain the etymology of the word (al)-muqawqis, which was used in early Arab Islamic historiography to designate a ruler of Alexandria and Egypt. After having summarized different interpretations of it, including the “Caucasian” one which corresponds to the career of the Chalcedonian Patriarch Cyrus appointed to Egypt in autumn of AD 631, the author decided to follow the steps of the famous Russian church historian V. V. Bolotov, who preferred to etymologize muqawqis in accordance with the Classical Arabic lexicography. The research sources are the two largest national Arabic dictionaries, the Lisân al-‘Arab (AD 1209) and the Tâdj al-‘Arûs (AD 1774). The author examines in detail the entries for the roots Q-Q-S and Q-W-Q-S. The particular attention is paid to a hadîth, which deals with the aftermath of the Battle of Uhud (March 23, AD 625) and to the participation of the Prophet Muhammad in the funeral of one of its heroes. The Messenger of God is said to ride a horse which was prancing under him (yataqawqasu). The author suggests here a parallel with the so-called “Equestrian saints” who were portrayed on levant horses and draws a conclusion that in certain contexts the word muqawqis could be applied to (Egyptian) aristocrats.